Next-Gen Workforce Meets AI: Navigating Career Paths in a Tech-Driven World - Kia Hui Gan; Lim Hui Ling; Liem Gai Sin; Sushmita A/P Kannan; Song Ruicen; Sun Danning; Sun Zexuan; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2025)
Artificial Intelligence (AI) is rapidly transforming the global world of work, raising important questions about how younger generations perceive its impact on their future careers. This study investigates the perceptions of Generation Y (Gen Y) and Generation Z (Gen Z) university students toward AI and its influence on employment opportunities. A quantitative survey was conducted with 150 respondents from universities in China and Malaysia, focusing on two key variables: AI awareness and perceptions of employment prospects. The results reveal that both cohorts generally demonstrate positive levels of awareness and optimistic attitudes toward AI. Notably, students’ attitudes were found to play a more significant role than awareness in shaping their views regarding AI’s potential effects on their future career opportunities. These findings underscore the importance of higher education institutions in enhancing AI literacy, cultivating adaptive mindsets, and integrating technology-oriented curricula to prepare students for the demands of an AI-driven labor market. By fostering proactive and confident engagement with emerging technologies, universities can empower future professionals to navigate challenges and leverage opportunities in the evolving digital economy.